Atomic-scale dynamics of triangular hole growth in monolayer hexagonal boron nitride under electron irradiation1. Issue 24 (28th June 2015) - Ryu, Gyeong Hee; Park, Hyo Ju; Ryou, Junga; Park, Jinwoo; Lee, Jongyeong; Kim, Gwangwoo; Shin, Hyeon Suk; Bielawski, Christopher W.; Ruoff, Rodney S.; Hong, Suklyun; Lee, Zonghoon
<x xml:space="preserve">Abstract</x> The production of holes by electron beam irradiation in hexagonal boron nitride is monitored over time using atomic resolution transmission electron microscopy.